3x-y=3 and 9x-y=4 by substitution method​

Question

3x-y=3 and
9x-y=4 by substitution method​

in progress 0
Genesis 5 months 2021-12-27T11:06:38+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-12-27T11:08:24+00:00

    Let us number the equations :

    3x-y=3 ........ (1)

    9x-y=4 ......... (2)

    Taking 1:

    \implies 3x-y=3

    {\underline{\boxed{\implies y=3x-3}}} ..(3)

    Taking 2:

    \implies 9x-y=4

    \implies 9x -(3x-3) =4

    \implies 9x-3x+3=4

    \implies 6x=4-3

    {\underline{\boxed{\red{.\degree.x=\frac{1}{6}}}}}

    Now from.... 1

    \implies 3x-y=3

    \implies 3\times\frac{1}{6}-y=3

    \implies \cancel{3}\times\frac{1}{\cancel{6}^{2}}-y=3

    \implies \frac{1}{2}-y=3

    \implies y = \frac{1}{2}-3

    \implies y =\frac{1-6}{2}

    {\underline{\boxed{\purple{.\degree. y=\frac{-5}{2}}}}}

    <marquee scrollamount="1300">♥Answer by Rishabh♥</marquee>

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )